2006
DOI: 10.1111/j.1532-5415.2006.00969.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Prevalence of Depressive Symptoms and Antidepressant Use Between 1988 and 1999 in a Large Sample of Older French People: Results from the Personnes Agées Quid Study

Abstract: This study suggests better management of late-life depression in the last decade and illustrates the heterogeneity of depression disorder in late life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 24 publications
3
18
0
Order By: Relevance
“…It is notable that both TCAs and SSRIs have been associated with fracture risk (8, 9), and in the CaMos cohort only 14.9% of men and 17.5% of women with depressive symptomatology reported daily use of one of these medications. This low rate of pharmacologic anti-depressant therapy among individuals with depressive symptoms is consistent with the findings of other large-scale studies in elderly populations (33, 34). Finally, it is possible that complications of low bone mineral density worsen the disease course of depression.…”
Section: Discussionsupporting
confidence: 91%
“…It is notable that both TCAs and SSRIs have been associated with fracture risk (8, 9), and in the CaMos cohort only 14.9% of men and 17.5% of women with depressive symptomatology reported daily use of one of these medications. This low rate of pharmacologic anti-depressant therapy among individuals with depressive symptoms is consistent with the findings of other large-scale studies in elderly populations (33, 34). Finally, it is possible that complications of low bone mineral density worsen the disease course of depression.…”
Section: Discussionsupporting
confidence: 91%
“…This increase was mainly due to the increase in use of SSRIs while use of TCAs remained stable over time. The French study PAQUID found an increase in antidepressant use from 5.2% in 1988-90 to 11.9% in 1998-99 in older people (Montagnier et al, 2006). The results are also consistent with the trends observed in other international longitudinal studies in the elderly population.…”
Section: Discussionsupporting
confidence: 88%
“…In the French study PAQUID, there was an increase in antidepressant use in both depressed and non-depressed respondents (Montagnier et al, 2006). However, among the participants without depressive symptoms, there may have been an increase in the use of antidepressants (5% at wave 1 and 12% at wave 7).…”
Section: Discussionmentioning
confidence: 94%
“…Studies on prevalence of depression in the elderly population have produced conflicting results with respect to context of daily living (Okwumabua et al, 1997;Kim et al, 2002;Wang, 2004;Montagnier et al, 2006;Probst et al, 2006;Friedman et al, 2007;Bergdahl et al, 2007). Some studies indicated higher prevalence of depression in urban areas than in rural areas (Paykel et al, 2003;Friedman et al, 2007); one hypothesis that may account for this result is that the social relationships, defined by their structural (social networks) and functional features (social support and conflict), of elderly persons living in rural areas and small cities differ from those of elderly persons living in metropolitan regions.…”
Section: Introductionmentioning
confidence: 98%